RELIGIOSITY OF THE MALAY BATUBARA TROUGH ANTHROPOLOGICAL AND HISTORICAL APPROACH - Maulana, Cecep; Loebis, Iin Almeina (BASIS (Bahasa dan Sastra Inggris), 2022)
This research is talked about the Islamic Religious Discourse of Malay Batu Bara. In this case, the researchers took the historic sites in Batu Bara as a support in the Islamic religion of Malay Batu Bara. Background with many historic sites Batu Bara which is considered by some people to have high noble values and touched to religious part of the community and make researcher interested to explore this anthropology history approach which found the contribution about various aspects of human life, society and culture but also showed  the procedure, technique and process. That is systematically arranged in disciplinary research to develop knowledge and obtain the object study. To implement this research the writer uses the methodology with a qualitative approach which results in descriptive data and the object under study is the Islamic religious of Malay Batu Bara. In collecting data researchers use the power of primary and secondary data. In analyzing the data researchers use data reduction, data presentation, and concluding that do data verification. Then in the validity of the data the researcher uses the degree of trustworthiness, dependability, and certainty. In the scientific , researchers use anthropology  history. Researchers found many historic sites in Batu Bara which are very close. They are Kubah Datok Batu Bara, Sumur Istana Niat Lima Laras and Meriam Bogak. From the three historic sites, the researcher found a theoretical component from religion as said by C.Y.Glock and R. Stark that is the dimension of faith, dimension ritualistic, dimension experiential, dimension consequential, and dimension intellectual. Besides that researchers also found religious Malay Batu Bara community also influenced by beliefs in occult things such as witchcraft, rituals rejecting reinforcements, sea spells, and also related to beliefs in traditions or customs such as abstinence forbids, tapai party and balimau bathing.